The Role Of Trust Between Partners In The Process Of Knowledge Acquisition Within Interational Joint Ventures - Hanachi, Mustapha Kamel (جامعة الوادي - University of Eloued, 2022)
In front ofthe environment disturbances in which firms exercise, and in order to ensure their continuity and competitiveness, managers must reorient their interest towards organizational learning through the accumulation of knowledge. Through the studyof the process of knowledge acquisition with in International Joint Ventures from partners, we try, through an exploratory approach, to discernthe determinants that may influence this process.We focus, in particular, on trust between partners that may havea significant effect on the processof knowledge acquisition and the aboved eterminants. This research producesa set of propositions likely tobe verified in futureexplanatoryresearch.
مقال
Keywords: : Organizational learning ; Knowledge acquisition ; International Joint Venture ; Trust between partners ; exploratory research